2015
DOI: 10.1002/2015gl065192
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of relationship between geosynchronous relativistic electron enhancements and magnetic storms

Abstract: We find evidence that magnetic storms are not only unnecessary for geosynchronous relativistic electron enhancements but also not directly relevant to the electron enhancements even if the enhancements are accompanied by magnetic storms. What is crucial for electron enhancements at geosynchronous orbit are sustained south‐oriented or north‐south fluctuating interplanetary magnetic field (IMF) Bz that drives sufficiently large substorm activity and small solar wind density Nsw that likely leads to low loss rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 23 publications
7
64
0
Order By: Relevance
“…4. Understanding the complex evolution of the outer radiation belt requires to explain in addition why similar geomagnetic storms can produce different levels of global energization or loss, as first noted by Reeves et al (2003) (see also more recent studies by Turner et al 2015;Kim et al 2015). As we show in this review, one likely cause, if not the sole one, can be the observed variability of lower-band chorus wave obliquity with geomagnetic activity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…4. Understanding the complex evolution of the outer radiation belt requires to explain in addition why similar geomagnetic storms can produce different levels of global energization or loss, as first noted by Reeves et al (2003) (see also more recent studies by Turner et al 2015;Kim et al 2015). As we show in this review, one likely cause, if not the sole one, can be the observed variability of lower-band chorus wave obliquity with geomagnetic activity.…”
Section: Discussionmentioning
confidence: 88%
“…A correlation between large enhancements of electron flux and D st has been observed at L 3-5.5 in the outer radiation belt (Zhao and Li 2013). However, other recent investigations have shown that D st alone cannot fully characterize the energization of electrons at higher L 6.6: there, AE and K p turn out to be much more discriminating, but solar wind parameters should be taken into account as well (Kim et al 2015). 3.…”
Section: Statistical Models Of Chorus Waves Derived From Satellite Obmentioning
confidence: 93%
See 1 more Smart Citation
“…Kim et al . [] have shown that relativistic electron enhancements at geosynchronous orbit likely occur independently from geomagnetic storms. Turner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al ., ; Reeves et al ., ; Boynton et al ., ; W . Li et al ., ; Kim et al ., ; Xiong et al ., ; Ni et al ., , ; Yu et al ., , ; Wing et al ., ]. However, these studies mainly discussed relativistic electron fluxes at geosynchronous orbit, which is well beyond the center of the outer radiation belt, and these changes of MeV electron fluxes included both nonadiabatic and adiabatic processes.…”
Section: Introductionmentioning
confidence: 99%